Contrasting distributions of dissolved gaseous mercury concentration and evasion in the North Pacific Subarctic Gyre and the Subarctic Front. (April 2016) - Kim, Hyunji; Rhee, Tae Siek; Hahm, Doshik; Hwang, Chung Yeon; Yang, Jisook; Han, Seunghee
Abstract: The distribution of dissolved gaseous mercury (DGM) and the oxidation–reduction processes of mercury (Hg) in the surface and subsurface ocean are currently understudied despite their importance in ocean–atmosphere interactions. We investigated the Hg(0) evasion and the DGM distribution at water depths of 2–500 m in the Subarctic Front, Western Subarctic Gyre, and Bering Sea of the Northwestern Pacific. The mean DGM concentration in the surface mixed water (<10 m) and the mean Hg(0) evasion flux were significantly higher in the Subarctic Front (125±5.0 fM and 15 pmol m −2  h −1, respectively), which typically has lower nutrient levels and higher primary production, than in the Western Subarctic Gyre and the Bering Sea (74±18 fM and 3.2±1.2 pmol m −2  h −1, respectively). The variation in the chlorophyll-a concentration and extracellular protease activity predicted 54% and 48% of the DGM variation, respectively, in the euphotic zone (2–50 m). The DGM concentration in aphotic intermediate water (415±286 fM) was positively correlated to the apparent oxygen utilization (AOU; r 2 =0.94 and p <0.001 for the Western Subarctic Gyre and the Bering Sea; r 2 =0.61 and p =0.01 fo r the Subarctic Front), emphasizing the importance of microbial oxidation of organic matter. The DGM-to-AOU ratio in aphotic water was significantly ( p <0.05, ANCOVA) higher at the Western Subarctic Gyre and Bering Sea sites (2.5±0.14) than the ratio at the Subarctic Front sites (0.89±0.27) that mainly consisted of newly formed North Pacific Intermediate Water. The overall results imply that variation of DGM and Hg(0) evasion is closely linked to primary production in euphotic water and organic remineralization in aphotic intermediate water. The oceanic alterations in these factors may induce significant modification in Hg redox speciation in the Northwestern Pacific. Highlights: We investigated DGM and Hg(0) flux in the subarctic front and subarctic gyre. Surface DGM and Hg(0) evasion were higher in subarctic front than subarctic gyre. Intermediate water DGM was higher in subarctic gyre than subarctic front. DGM and Hg(0) evasion was closely linked to phytoplankton biomass in euphotic water. DGM concentration in aphotic water was positively correlated to AOU.